Effects of fatty acid metabolites on nocturia - Ihara, Tatsuya; Shimura, Hiroshi; Tsuchiya, Sachiko; Kanda, Mie; Kira, Satoru; Sawada, Norifumi; Takeda, Masayuki; Mitsui, Takahiko; Shigetomi, Eiji; Shinozaki, Yoichi; Koizumi, Schuichi (Scientific reports, 2022)
Dysregulation of circadian rhythm can cause nocturia. Levels of fatty acid metabolites, such as palmitoylethanolamide (PEA), 9-hydroxy-10E,12Z-octadecadienoic acid (9-HODE), and 4-hydroxy-5E,7Z,10Z,13Z,16Z,19Z-docosahexaenoic acid (4-HDoHE), are higher in the serum of patients with nocturia; however, the reason remains unknown. Here, we investigated the circadian rhythm of fatty acid metabolites and their effect on voiding in mice. WT and Clock mutant ( Clock Δ19/Δ19 ) mice, a model for nocturia with circadian rhythm disorder, were used. Levels of serum PEA, 9-HODE, and 4-HDoHEl were measured every 8 h using LC/MS. Voiding pattern was recorded using metabolic cages after administration of PEA, 9-HODE, and 4-HDoHE to WT mice. Levels of serum PEA and 9-HODE fluctuated with circadian rhythm in WT mice, which were lower during the light phase. In contrast, circadian PEA and 9-HODE level deteriorated or retreated in Clock Δ19/Δ19 mice. Levels of serum PEA, 9-HODE, and 4-HDoHE were higher in Clock Δ19/Δ19 than in WT mice. Voiding frequency increased in PEA- and 4-HDoHE-administered mice. Bladder capacity decreased in PEA-administered mice. The changes of these bladder functions in mice were similar to those in elderly humans with nocturia. These findings highlighted the novel effect of lipids on the pathology of nocturia. These may be used for development of biomarkers and better therapies for nocturia.